Molecular imprinting of dibenzothiophene using vinyl pyridine monomers: Fabrication and performance. Issue 10 (26th October 2016) - Chen, Li; Sun, Hui; Zhong, Yonghui; Zhang, Kaiyu; Zheng, Tiantian; Lin, Ligang; Cheng, Bowen
ABSTRACT: Molecular imprinting process was proposed for the sulfur removal from fuels. The novel network‐structured molecularly imprinted polymers (MIPs) were fabricated by arranging 4‐vinyl pyridine functional monomers around dibenzothiophene template compounds, and fixing them with ethylene glycol dimethacrylate as crosslinking agent. The effects of dispersed phase, washing after treatment, content of template molecule, and crosslinking agent on the recognition ability of MIPs have been investigated. The practical performance is obtained by the FT‐IR, morphology, and thermal analysis as well as the recognition ability for dibenzothiophene under various feed sulfur concentrations and recognition time. The recognition ability of MIPs under 1000 mg/L feed sulfur concentration was 4.53 mg S/g. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44552. Abstract :